Hubungan Dukungan Istri Dengan Pemilihan Kontrasepsi Metode Operasi Pria Di Kecamatan Abiansemal - I Gusti Ayu Adnya Saraswati; Ni Gusti Kompiang Sriasih; Ni Luh Putu Sri Erawati (Poltekkes Kemenkes Denpasar, 2019)
Male Operation Method is a contraceptive tool that has the lowest coverage in Indonesia including Bali. Low use of contraceptives Male Operation Methods are caused by three factors: predisposing factors, driving factors and supporting factors. Purpose of this study was determine the relationship of support the wife with choice of contraceptive male operation method in Abiansemal District. This was an observational analytic study with cross sectional design. The sample size in this study was 46 people. Sampling technique used is Nonprobability Sampling with Purposive sampling technique. Data analysis techniques using Chi Square test with hypothesis test through drawing conclusion based on p value at 95% confidence level. The results showed that wife support is a factor influencing the choice of contraception of Male Operation Method. The higher the support provided, the higher the choice of contraceptive methods of Male Operation, and vice versa. The analysis results obtained that if Chi square count (5,489) Chi square table (3,841) or p-value (0,019) α (0,05). There is a significant relationship between the support of the wife with the choice of contraception Method of Operation Men in Abiansemal District. Conclusion of the research that there is a relationship between the support of the wife with the choice of contraception Method Operation Man in Abiansemal District. Health workers and BKKBN officers expected to provide health education about contraceptive male operation method widely.Keywords: wife support; contraceptive selection; male operation method.